2000
DOI: 10.1038/sj.bjp.0703386
|View full text |Cite
|
Sign up to set email alerts
|

Role of A2A‐adenosine receptor activation for ATP‐mediated coronary vasodilation in guinea‐pig isolated heart

Abstract: 1 Adenosine-5'-triphosphate (ATP) and adenosine are potent coronary vasodilators. ATP is rapidly converted to adenosine by ectonucleotidases. We examined whether coronary vasodilation caused by exogenous ATP is mediated by P 2 receptor activation or by A 2A -adenosine receptor activation. 2 E ects of interventions on coronary conductance were determined by measuring coronary perfusion pressure in guinea-pig isolated hearts perfused at a constant¯ow of 10 ml min 71 . 3 ATP and adenosine both caused sustained, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 54 publications
3
15
0
Order By: Relevance
“…16,25–27 Accordingly, we investigated the role of direct ATP signaling in US-mediated augmentation of perfusion. Administration of apyrase as an exogenous CD39-like nucleotidase that rapidly degrades ATP did not change blood flow response to US cavitation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…16,25–27 Accordingly, we investigated the role of direct ATP signaling in US-mediated augmentation of perfusion. Administration of apyrase as an exogenous CD39-like nucleotidase that rapidly degrades ATP did not change blood flow response to US cavitation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Gödecke et al [23]suggested that vasodilation at these concentrations is due only to ATP-induced P 2Y -receptor activation, whereas Korchazhkina et al [15]proposed that both adenosine and ATP exert a vasodilatory effect. Erga et al [24], in isolated guinea pig heart, suggested that vasodilation caused by exogenous ATP is only adenosine dependent.…”
Section: Discussionmentioning
confidence: 99%
“…In general, ATP and ADP elicit EC-dependent dilation in a variety of vasculatures in several species. Proposed mediators include nitric oxide (NO), prostacyclin (PGI 2 ), endothelium-derived hyperpolarizing factor (EDHF) 3,4 , P2 purinoceptors 5 , and P1 (adenosine) receptors 6 . Thus it is likely that the mechanisms involved are largely dependent upon either receptor-mediated EC activation or the hydrolysis kinetics of adenine nucleotides in vasculatures.…”
Section: Introductionmentioning
confidence: 99%